2009 9th International Symposium on Communications and Information Technology 2009
DOI: 10.1109/iscit.2009.5341177
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation scheme with proportional fairness for multi-user downlink MIMO-OFDMA-CDM systems

Abstract: In this paper, we propose a new resource allocation scheme that enhances a diversity effect with taking into account a proportional fairness (PF) in downlink MIMO-OFDMA-CDM (multiple input multiple output -orthogonal frequency division multiple access -code division multiplexing) systems. In the proposed scheme, spectral resources are allocated per subcarrier unit and full code-spreading is done for each user using all allocated subcarriers. This maximizes a frequency diversity effect and also enhances a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…SA also uses the same fitness function shown in fig-5 and described in Equ. (8). In order to find the optimum power vector, the basic flat power vector (initial guess) is passed through the OFDM system.…”
Section: B Simulated Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…SA also uses the same fitness function shown in fig-5 and described in Equ. (8). In order to find the optimum power vector, the basic flat power vector (initial guess) is passed through the OFDM system.…”
Section: B Simulated Annealingmentioning
confidence: 99%
“…Also it was shown that GA is better than conventional methods. A scheme for resource allocation in downlink MIMO-OFDMA with proportional fairness where dominant Eigen channels obtained from MIMO state matrix are used to formulate the scheme with low complexity in [8], scheme provides much better capacity gain than static allocation method. A PSO based Adaptive multicarrier cooperative communication technique which utilizes the subcarrier in deep fade using a relay node in order to improve the bandwidth efficiency [9] where centralized and distributed versions of PSO were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A scheme for resource allocation in downlink Multiple Input Multiple Output (MIMO) OFDMA with proportional fairness where dominant Eigen channels obtained from MIMO state matrix are used to formulate the scheme with low complexity in [22], scheme provides much better capacity gain than static allocation method. A PSO based Adaptive multicarrier cooperative communication technique which utilizes the subcarrier in deep fade using a relay node in order to improve the bandwidth efficiency [23] where centralized and distributed versions of PSO were investigated.…”
Section: Introductionmentioning
confidence: 99%